Implementasi Data Warehouse dan Business Intelligence Menggunakan Pentaho dan Metabase untuk Membuat Dahboard Visualisasi Kinerja Penjualan E-Commerce Wish - Murtiwiyati Murtiwiyati; Hansel Agathon; Leli Safitri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
As a business develops, the volume of data generated also increases. With the amount of data that continues to grow, it is necessary to process data that can support the improvement of the quality of business processes. Data processing on Wish can be done by implementing the Extract, Transform, Load process in the data warehouse using Pentaho and visualizing business intelligence with a dashboard using Metabase. The data used in this research is Wish transaction data for the period 2020-2023. The results of this study are a data warehouse using a PostgreSQL database and a dashboard to display Wish's sales performance. The results of the analysis of Wish's sales performance show that during 2020-2023 sales have increased, but most of these sales only come from one country, namely the United States. Therefore, Wish needs to make new innovations to attract customers from other countries.